SUCCESS FACTORS OF AN ENTERPRISE UNDER CRISIS - Y. V. Danilina (Russian Journal of Economics and Law)
Objective: to analyze the impact of economic crisis in Russia on the enterprises’ access to productive resources, as well as on the level of their competencies.Methods: historical, abstract-logical.Results: the article states that, despite the influence of external factors, the main activities of the company are internal capabilities and resources of the firm. It is shown that under crisis a company must adapt to the limited resources, i.e. change the competences of using them. Under modern conditions the competitive advantage can be based on two components - access to resources and internal ability of the company to use them. Therefore, under the resource constraints such competencies should be generated as: 1) ability to use a smaller amount of resources; 2) more efficient use of available resources; 3) search for the new resources, development of own resources.The study determined that the acquisition of new competencies by the company will be associated with the use and improvement of its cognitive capabilities, which are a function of organizational and individual knowledge possessed by the enterprise, i.e. its intellectual capital.The article analyses the experience of development of new competencies under crisis by the example of reorganization of "Prompribor" plant and activities of "Galogen" JSC. Analysis of the experience of these companies, which not only survived during the crisis, but also acquired new competences and skills, have led to the conclusion that the key role in this process was played by working with the main part of a company's intellectual capital, i.e. human capital. Thus, a conclusion is made about the value of people and their common interests during the transformations within the enterprise.Scientific novelty: for the first time the cognitive aspects of the enterprises’ modernization system are considered from the viewpoint of the new resource and competence theory of the enterprise.Practical significance: the main provisions and conclusions of the article can be used in the development or adjustment of the enterprises’ modernization strategy under economic crisis.